BALBINOTTI SCALE OF FUTURE PERSPECTIVES OF MOTIVATION FOR ATHLETES (EBMPFA-15): EVIDENCE OF VALIDITY BASED ON THE INTERNAL STRUCTURE OF THE CONSTRUCT AND RELIABILITY - Daniela Wiethaeuper; Leonardo Pestillo de Oliveira; Evandro Morais Peixoto; Marcos Alencar Abaide Balbinotti; Ricardo de Almeida Castillo (Journal of Physical Education)
ABSTRACT This research aimed to test the three-dimensional model - Orientation to Pleasure by Learning (OPA); Orientation to Dedication and Enthusiasm (ODE); Orientation to circumstantial Motivation (WTO) - evaluated by Balbinotti Scale of Future Perspectives of Motivation for Athletes (EBMPFA-15). Sample: 707 regular physical activity practitioners, male and female, aged between 12 and 33 years. Results: Exploratory (61.1% of the total variance of the construct) and confirmatory factor analysis (χ2 / df = 3.99; CFI = 0.97, TLI = 0.96; RMSEA = 0.06; 90% CI = 0.05 to 0.07) corroborate the three-dimensionality and the suitability of the tested model to evaluate men and women (invariance). The Alpha, Omega and GLB indices (0.70 to 0.89) ensure its reliability. In conclusion the instrument has satisfactorily first evidence of validity and internal stability, as well as the accuracy of the theoretical model measure. Further studies should test other evidence of validity and interpretative rules of EBMPFA-15.